2003
DOI: 10.1002/cncr.11070
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen‐gauge needle core biopsy of mammographically evident radial scars

Abstract: The effect of pH on the precipitation of soy protein between pH 4 and 6.8 was investigated. Precipitation between pH 5.7 and 6.8 gave a binary liquid‐liquid separation in which a protein‐rich secondary liquid phase containing between 20 – 30 wt % protein of 80 – 99% purity in glycinin formed as droplets of 1 – 10 μm. The droplets could be coalesced upon centrifugation to form a homogeneous bottom liquid layer. The high‐protein concentration phase was stable (did not precipitate or crystallize) for up to severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 37 publications
6
65
2
6
Order By: Relevance
“…10,13,[27][28][29] When we excluded cases associated with epithelial atypia (PPV ¼ 39%) from the analysis, the PPV of RS/CSL was 9%, similar to that reported in our previous study (9%). 4 These findings in addition to the fact that most of the malignant lesions detected after a diagnosis of RS/CSL were low grade (80%) and often of pure tubular morphology (55%) may support consideration of nonsurgical management, such as removal by vacuum assisted biopsy, in selected cases.…”
supporting
confidence: 86%
“…10,13,[27][28][29] When we excluded cases associated with epithelial atypia (PPV ¼ 39%) from the analysis, the PPV of RS/CSL was 9%, similar to that reported in our previous study (9%). 4 These findings in addition to the fact that most of the malignant lesions detected after a diagnosis of RS/CSL were low grade (80%) and often of pure tubular morphology (55%) may support consideration of nonsurgical management, such as removal by vacuum assisted biopsy, in selected cases.…”
supporting
confidence: 86%
“…In an overview of this topic, Jacobs et al (2002) reported that knowledge and consensus on the management of these lesions are hindered by the very small number of subjects in most studies, and also by selection bias for subjects managed with excision biopsy (Jacobs et al, 2002). Whereas acknowledging that a few studies have included more cases per specific B3 lesion (Cawson et al, 2003;Shah et al, 2006), we believe that our study addresses the first issue in providing the largest consecutive study of B3 cases. As for the latter issue, and while selection to surgery was not entirely avoided, the vast majority of subjects had excision in our series.…”
Section: Discussionmentioning
confidence: 91%
“…5 However, it has also been suggested that pure radial scars diagnosed by needle core biopsy do not require excision and can be managed safely by mammographic surveillance. 6 There are mammographic features suggestive of radial scars (for example, the Tabar and Dean criteria; Table 2). 2 However, only 68% of radial scars present as a typical mammographic lesion and less than 50% display all the Tabar and Dean criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six invasive cancers identified on excision biopsy, four were thought to be pure radial scars on needle core biopsy (67%). In addition there were 22 lesions (18%) with associated atypia -ADH (13), ALH (6) and both ADH and ALH (3) -and, finally, three cases (2.5%) with LCIS. Only 81 lesions were deemed to be pure radial scars on final histological assessment, giving an overall false negative rate of 12% for needle core biopsy.…”
Section: A Review Of Needle Core Biopsy Diagnosed Radial Scars In Thementioning
confidence: 98%